Peran Orang Tua Terhadap Pendidikan Spiritual Anak - Novina Lenggu (Universitas Katolik Widya Karya Malang, 2023)
Spiritual education is an important aspect of a child's holistic development, which involves understanding religious values, beliefs, and practices. Parents play a crucial role in shaping and facilitating the spiritual education of their children. This abstract discusses the important role of parents in supporting and promoting children's spiritual education, as well as the implications for children's development. This study was conducted through a literature review and analysis of previous research. The results showed that parents act as role models and role models for their children. They can provide spiritual education by teaching moral values, involving children in religious activities, and providing an understanding of family religious beliefs and practices. In addition, open and deep communication between parents and children also plays an important role in spiritual education. Discussions about beliefs, values, and spiritual questions can help children understand and internalize spiritual principles. The role of parents in children's spiritual education has a significant impact on children's development. Children who get good spiritual education tend to have a better understanding of moral values, a sense of empathy, and a sense of connectedness with others. They also have a higher tendency to develop a positive attitude towards life, are able to overcome challenges, and have better psychological well-being.